“REORGANIZACIÓN ADMINISTRATIVA Y CONTABLE EN LA EMPRESA COMERCIAL Y DE SERVICIOS “GLOBALIMPIO CIA. LTDA” DE LA CIUDAD DE LOJA, PERIODO DEL 01 DE SEPTIEMBRE AL 31 DE DICIEMBRE DEL 2020.” - Flores Alemán, Lizbeth Katherine (2021)
The thesis work entitled "ADMINISTRATIVE AND ACCOUNTING REORGANIZATION IN THE COMMERCIAL AND SERVICES COMPANY "GLOBALIMPIO CIA. LTDA." OF THE CITY OF LOJA, PERIOD FROM SEPTEMBER 1 TO DECEMBER 31, 2020"; has the purpose of improving the administrative and accounting management through a reorganization that adapts to the needs of the company, obtaining as a result a business management that helps to meet the objectives that were established at the beginning of the administrative and operational activities of the business. In order to fulfill the proposed objectives, different research methods and techniques were used to obtain real information about the internal situation of the company; Interviews and direct observations were applied, which evidenced delays in the execution of administrative and operational processes, so that, in order to provide a solution to these problems, a functional organization chart, a manual of functions and procedures, flowcharts and control records indicating the process of the most relevant activities in the company, all this in order to facilitate the execution and management of work by establishing the levels of command and the functions to be performed in the different positions held by the staff, were developed. As for the procedures applied to comply with the accounting objectives, the first step was the physical verification of all assets, values, rights and obligations to prepare and structure the Initial Inventory. Parallel to this, a plan and manual of accounts was prepared according to the nature and policies of the company, based on the format established by the Superintendence of the Company, therefore, this allowed the company to have a better control over the accounting of its daily economic operations. Likewise, in order to prepare the different auxiliary records, such as sales, purchases, accounts receivable, accounts payable and payment roles, we proceeded to order, analyze and interpret all the documentation that supports the transactions carried out by the 5 company. Then, with the information synthesized in the auxiliary accounting records, the operations began to be recorded chronologically in the Daily Book, General Ledger, Trial Balance, Worksheet and culminated with the presentation of the Financial Statements, which resulted in the following values for the company as of December 31, 2020: Revenues $47. 010.58; Expenses $35,273.14; Net Profit for the Period $7,756.49; Assets $ 36,726.29; Liabilities $ 11,493.26 and Equity $ 25,233.03. . Finally, to fulfill the last objective of this thesis work, the financial indicators were applied, which showed that the company has a liquidity of $1.70 for every dollar it owes, that is, it has enough money to cover its short-term obligations, and also, with money to invest in new growth ideas; on the other hand, they maintain a debt level of 31.29% and a profit margin of 12.13%, which shows that at the moment the company has sufficient economic resources to continue to maintain a normal development of its economic activity. At the conclusion of the thesis work, it is determined that the application of an accounting and administrative reorganization in the company was of vital importance, since in the first place it allowed establishing improvements in its administrative process with the objective of maintaining a good performance in the performance of the functions of each labor position, while on the other hand, it provided accounting processes and techniques that facilitated the orderly and clear registration of daily activities giving the possibility of obtaining greater economic benefits at the end of the accounting period.